DIVERSIFIKASI TALAS BOGOR (Colocasia Esculenta (L) Schott) SEBAGAI UPAYA OLAHAN PRODUK TAPAI KHAS BOGOR - Antony Rendi Sanjaya; Ade Heri Mulyati; Padmono Citroreksoko (Universitas Pakuan, 2018)
In Bogor district as an Indonesian taro central production, recorded that it has almost 57000 ton taro each year in 2008. Bogors taro which is abundant in Bogor is still limited its use. Diversity the use of taro necessary to maximize available resources and make it becoming alternative processed products in market. Carbohydrat content in Bogors taro depends on data from Nutrition Directorate of Ministry of Health in 2008 is 23.79%, the high content of carbohydrate makes taro can be processed to a characteristic food such as tapai. This research aims to knowing type of taros effect to product and optimum fermentation time to make best tapai product. Research method begins with making tapai from three kind of taro, they are bentul taro, mentega taro and sutra taro. Then it fermentated at different time length, 48 hours, 72 hours and 96 hours. After get the best product that liked by the panellist, conducted quality testing seen from moisture, ash content, total fat, protein, pH, reduction sugar, carbohydrate content, alcohol content and dietary fibre. Tapai bentul taro with fermentation length 48 hours is chosen and it use as a remain variable. The result of chemical analysis tapai bentul taro (B1) are moisture 59.27%, ash content 2.11%, total fat 1.78%, protein 2.96%, pH 5.48, reduction sugar 12.13%, carbohydrate 21.94%, alcohol 6.03% and dietary fibre 2.28%.